Self-Efficacy Assessment of New Students in the Islamic Education Guidance and Counseling Study Program Sultan Syarif Kasim Riau State Islamic University Academic Year 2025/2026 (International Seminar of Islamic Counseling and Education Series Proceeding, 2025)
This study aims to describe the level of self-efficacy of new students in the Islamic Education Guidance and Counseling Study Program (BKPI) at UIN Sultan Syarif Kasim Riau for the 2025/2026 academic year. The research method used a quantitative descriptive approach with a Likert scale questionnaire consisting of 25 statement items. The validity of the instrument was tested using Pearson Product Moment correlation and reliability using Cronbach's Alpha, which showed reliable results (α = 0.832). The research subjects consisted of 125 new students, and the data were analyzed using descriptive statistics using SPSS. The results showed that the majority of respondents had high (46%) and very high (31%) self-efficacy. Meanwhile, 21% were in the moderate category, 2% were low, and 1% were very low. These findings confirm that most new BKPI students already have positive self-confidence to face academic and social demands in college. However, the existence of a small group of students with moderate to very low self-efficacy indicates the need for special assistance strategies. The implications of this study emphasize the importance of self-efficacy strengthening programs, such as academic coaching, learning skills workshops, mentoring, and counseling services, so that all students can adapt optimally and develop professional readiness as prospective counselors